Topological Defect-Regulated Porous Carbon Anodes with Fast Interfacial and Bulk Kinetics for High-Rate and High-Energy-Density Potassium-Ion Batteries - Huang, Junlong (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.